2005
DOI: 10.1007/s10705-005-2650-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Fractionation and Sorption in P-enriched Soils of Norway

Abstract: Phosphorus (P) enrichment can lead to imbalance in nutrient availability and pollution of terrestrial and aquatic ecosystems. Hence studies were carried out to investigate fractionation and sorption of P in eleven P-enriched soils collected from different agro-climatic sites in Norway. Different P fractions viz. total, organic, inorganic (easily soluble P, Fe-P, Al-P, Ca-P and occluded P), P w (water extractable), and NH 4 -lactate extractable P (P AL ) at the beginning and after the completion of the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Hydraulic load and Table 4. Amount (based on dry matter) and proportion of organic phosphorus (P) and sequentially extracted inorganic P fractions according to Singh et al (2005) for the accumulated sediment for the entire S. Stene wetland, inlet area and the mean of two shallow vegetated areas (Typha 1 and Typha 2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydraulic load and Table 4. Amount (based on dry matter) and proportion of organic phosphorus (P) and sequentially extracted inorganic P fractions according to Singh et al (2005) for the accumulated sediment for the entire S. Stene wetland, inlet area and the mean of two shallow vegetated areas (Typha 1 and Typha 2). …”
Section: Resultsmentioning
confidence: 99%
“…The different P i fractions were separated with a sequential fractionation procedure (for details, see Singh et al (2005)). P i was divided into 1) NH 4 Cl-P = bioavailable P, 2) NH 4 F-P = aluminum-bound P, 3) NaOH-P = P bound to iron-oxides, and 4) H 2 SO 4 -P = calcium-bound P.…”
Section: Sediment Sampling and Analysismentioning
confidence: 99%
“…Comparable correlations of PSC with Fe ox and Al ox have been reported in the literature [24,27,33,46,54,87,[89][90][91][92]. Numerous studies [22,29,46,89,93] have shown that the most important parameters that determine the P sorption are Fe ox and Al ox . The strong correlations between Fe ox and Al ox as well with the sum of Fe ox + Al ox as noted by Freese et al [22] make it difficult to assess the single importance of one of these fractions for P sorption by means of regression analysis.…”
Section: Soil P Sorption Kineticsmentioning
confidence: 86%
“…The greater P release from soil at R14 site compared to that under the young plantations may likely be associated with the Fe ox and Al ox phases in the soils. It was previously reported that the desorbable soil P was related to Fe ox and Al ox in sandy soil [27,29,93,103]. Moreover, study of Daly et al [29] and Nafiu [36] indicated that the sum of Fe ox and Al ox was the most important soil properties influencing the rate of P desorption.…”
Section: Soil P Sorption Kineticsmentioning
confidence: 90%
See 1 more Smart Citation